Pennsylvania Sentencing Data, 1977, 1980, 1983 ([Verlag nicht ermittelbar], 1985)
This data collection contains information on sentencing decisions in Pennsylvania for three years: 1977, 1980, and 1983. The 1977 data are based on separate 12-percent random samples of sentences selected from each of Pennsylvania's 67 counties. The 1980 data were collected in 23 of Pennsylvania's 67 counties. The sampling strategy varied by county, and a description is included in the codebook. The 1983 data are based on sentencing guideline forms submitted to the Commission by sentencing judges. The data include sentences imposed for felony and misdemeanor offenses, excluding driving under the influence. All three files contain demographic information, including defendant's sex, race, age, prior record, offense charge, sentences imposed, weapon usage, victim information, and socioeconomic status.